UNDER & POSTGRADUATES NURSING STUDENTS’ SATISFACTION WITH ACADEMIC ADVISING MANAGEMENT: A COMPARATIVE STUDY - Shreen Gaber Mohammed , (The Malaysian Journal of Nursing (MJN), 2021)
Introduction: Academic advising is very crucial part of Credit Hours System implementation and have abundant responsibilities for advising, sharing all faculty students' plans of their courses registration favorably and generously. Aim: This study aimed to assess the students’ satisfaction regarding management the academic advising processes and examine the satisfaction difference between under and postgraduates’ levels: design: A comparative descriptive research design was implemented. Sample: a cross-sectional sample of university nursing students. Tools: student’s satisfaction self-administered questionnaire was used. Results: The main discoveries of this study revealed that there was a statistically significant difference between under and postgraduates’ levels regarding their satisfaction T= (11.024), P = (0.000). Also, the study illustrated that there was a significant difference between their age and their satisfaction F= (6.94), P = (0.001). While there was no difference in their gender and their satisfaction scores T = (0.660), P = (0.50). Conclusion: Based on the results of the current study, it can be concluded that the overall level of satisfaction among Students is not enough to be satisfied, there is a difference between under and postgraduate in their levels of satisfaction. Recommendations: The advisor should not be changed frequently as it can be understood that faculty turnover can lead to problems, as well the management must be cautious about this issue and must ensure those good advisors are retained.